Diversification of Coconut Water as an Isotonic Drink in Katumbangan Lemo Village, Polewali Mandar Regency: Diversifikasi Air Kelapa Sebagai Minuman Isotonik Di Desa Katumbangan Lemo Kabupaten Polewali Mandar - Nurul Hidayah; Musrifah Tahar; Ayu Indayati Ismail (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The success of a village can be seen from the creation of a clean, safe, healthy environment and more independent in terms of economy. This will certainly be successful if there is good cooperation between the government, academics and also the village community. One of the collaborative activities carried out is in the utilisation of natural resources through processing coconut fruit that grows abundantly in Katumbangan Lemo village, Polewali Mandar Regency. The purpose of this activity is to educate the community to be able to diversify young coconut water into isotonic drinks that are healthy and economically valuable. The average evaluation results obtained showed more than 90% of the community strongly agreed on each indicator. These results indicate that the community can accept well the service activities carried out.